Implication of oxidative stress in the pathogenesis of systemic sclerosis via inflammation, autoimmunity and fibrosis - Ludivine Doridot; Mohamed Jeljeli; Charlotte Chêne; Frédéric Batteux (Redox Biology, 2019)
Systemic sclerosis is an autoimmune disorder characterized by inflammation and a progressive fibrosis affecting the skin and visceral organs. Over the last two decades, it became clear that oxidative stress plays a key role in its pathogenesis. In this review, we highlighted the role of ROS in the various pathological components of systemic sclerosis, namely the inflammatory, the autoimmune and the fibrotic processes. We also discussed how these pathological processes can induce ROS overproduction, thus maintaining a vicious circle. Finally, we summarized the therapeutic approaches targeting oxidative stress tested in systemic sclerosis, in cells, animal models and patients.